The IASLC Lung Cancer Staging Project: Proposals for the Revisions of the T Descriptors in the Forthcoming Eighth Edition of the TNM Classification for Lung Cancer. Issue 7 (July 2015) - Rami-Porta, Ramón; Bolejack, Vanessa; Crowley, John; Ball, David; Kim, Jhingook; Lyons, Gustavo; Rice, Thomas; Suzuki, Kenji; Thomas, Charles F.; Travis, William D.; Wu, Yi-Long
Abstract : Introduction: An international database was collected to inform the 8 th edition of the anatomic classification of lung cancer. The present analyses concern its primary tumor (T) component. Methods: From 1999 to 2010, 77, 156 evaluable patients, 70, 967 with non–small-cell lung cancer, were collected; and 33, 115 had either a clinical or a pathological classification, known tumor size, sufficient T information, and no metastases. Survival was measured from date of diagnosis or surgery for clinically and pathologically staged tumors. Tumor-size cutpoints were evaluated by the running log-rank statistics. T descriptors were evaluated in a multivariate Cox regression analysis adjusted for age, gender, histological type, and geographic region. Results: The 3-cm cutpoint significantly separates T1 from T2. From 1 to 5 cm, each centimeter separates tumors of significantly different prognosis. Prognosis of tumors greater than 5 cm but less than or equal to 7 cm is equivalent to T3, and that of those greater than 7 cm to T4. Bronchial involvement less than 2 cm from carina, but without involving it, and total atelectasis/pneumonitis have a T2 prognosis. Involvement of the diaphragm has a T4 prognosis. Invasion of the mediastinal pleura is a descriptor seldom used. Conclusions: Recommended changes are as follows: to subclassify T1 into T1a (⩽1 cm), T1b (>1 to ⩽2 cm), and T1c (>2 to ⩽3 cm); to subclassify T2 into T2a (>3 to ⩽4 cm) and T2b (>4 to ⩽5 cm); to reclassify tumors greater than 5 to less than or equal to 7 cm as T3; to reclassify tumors greater than 7 cm as T4; to group involvement of main bronchus as T2 regardless of distance from carina; to group partial and total atelectasis/pneumonitis as T2; to reclassify diaphragm invasion as T4; and to delete mediastinal pleura invasion as a T descriptor.